Electrolyte Replacement in Bartter Syndrome With Abnormal Small Bowel: A Case Report - Philip T. Sobash MD; Krishna Vedala MD, MPH; Charles M. McClain MD; Caleb Oster DO (SAGE Publishing, 2020)
Bartter syndrome is a rare disorder that is characterized by weakness and fatigue with laboratory findings of hypokalemia and metabolic alkalosis with increased aldosterone and angiotensin. It specifically acts on the ascending loop of Henle, characterized by miscoded proteins affecting NaCl transports and channels. Patients will require replacement of potassium and sometimes magnesium due to the kidneys' inability to reabsorb these ions. So what happens when the body's other primary mechanism of absorption of these elements are taken out? In this article, we present the case of a 47-year-old woman with Bartter syndrome on oral potassium 40 mg BID (twice a day) and magnesium oxide 800 TID (thrice a day), who recently had a small bowel resection that required intravenous potassium and magnesium throughout her hospital admission. Significant questions arose as to how her electrolytes should be managed, given her unusual presentation with rare underlying disorder. We discuss the implications of her bowel resection in the context of Bartter syndrome and our views on her future course based on available literature.